2021
DOI: 10.3390/polym13142264
|View full text |Cite
|
Sign up to set email alerts
|

Impact Resistance of Epoxy Composites Reinforced with Amazon Guaruman Fiber: A Brief Report

Abstract: Fibers extracted from Amazonian plants that have traditionally been used by local communities to produce simple items such as ropes, nets, and rugs, are now recognized as promising composite reinforcements. This is the case for guaruman (Ischinosiphon körn) fiber, which was recently found to present potential mechanical and ballistic properties as 30 vol% reinforcement of epoxy composites. To complement these properties, Izod impact tests are now communicated in this brief report for similar composites with up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In these figures, the fracture mechanisms that occurred are associated with the rupture of microfibrils that provide an additional free surface and have the ability to increase the energy of the absorbed impact. This same effect was reported by Reis et al [ 39 ] when evaluating the energy of impact absorbed by guaruman fiber-reinforced epoxy matrix composites.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In these figures, the fracture mechanisms that occurred are associated with the rupture of microfibrils that provide an additional free surface and have the ability to increase the energy of the absorbed impact. This same effect was reported by Reis et al [ 39 ] when evaluating the energy of impact absorbed by guaruman fiber-reinforced epoxy matrix composites.…”
Section: Resultssupporting
confidence: 86%
“…In this first preliminary work on the characterization and properties of TVF composites, the matrix was selected as the same DGEBA/TETA epoxy, which has been successfully considered for other Amazon native NLFs [ 38 , 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have revealed an increase in the search for NLFs that can be used to reinforce polymeric composites, among which those found in the Amazon region stand out [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]; for instance, curaua [23,29], buriti [19,30], mallow [27,35], carnauba [38] and titica vine [39]. In addition to Amazon fibers, several other NLFs are being studied as possible reinforcements for polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that hybrid composites are much more stable than single-filler composites. Raphael et al [23] investigated the Impact Resistance of fibre Amazon fibre-fortified epoxy resin composite materials. It was observed that there is an increase in impact strength when volume fraction at 30% of Guaruman fibre content, which is better than pure epoxy.…”
Section: Introductionmentioning
confidence: 99%